Konflik Pemanfaatan Sumber Daya Perikanan Antara Indonesia Dan China Di Laut Natuna - Daniel Nazareth Soplera; Josina Augustina Yvonne Wattimena (Faculty of Law, Universitas Pattimura, 2021)
Introduction: This study discusses the conflict in the use of fishery resources between Indonesia and China in the Natuna sea.Purposes of the Research: To show the provisions of the international legal area regarding the boundaries of the exclusive economic zone in the Natuna islands belonging to Indonesia which china claims as its own.Methods of the Research: This research uses the notmative legal research method which is carried out by examining legal materials related to the problem being studied.Results of the Research: The results of the study show that the conflict in the use of fisheries resources between Indonesia and China in the Natuna sea which is claimed by China based on the nine-dash line and traditional fishing ground is an unfounded reason. Because, in 1982 UNCLOS did not recognize the nine-dash line and the traditional fishing ground. Thas’s why Indonesia does a persistent objection through a diplomatic note, if Indonesia is considered to have complied with the nine-dash line and traditional fishing ground rules declared by china.